Kontroversi Sejarah La Mohang Daeng Mangkona dan Hari Jadi Kota Samarinda: Sebuah Tinjauan Kritis - Muhammad Sarip; Nabila Nandini (Yupa: Historical Studies Journal, 2021)
The establishment of Samarinda on January 21st, 1668 which was set out by the Regional Government of the Municipality of Samarinda in Regional Regulation Number 1 of 1988, has been a controversy. The historical milestone of the establishment was based on the arrival event of a group from Sulawesi Island to Samarinda. Selection of this event disregards the traditional historiography record of an ancient Kutai local community which where exist long before the Bugis settlement in Samarinda Seberang. This study aims to analyse the historical validity of the arrival of La Mohang Daeng Mangkona's entourage in Samarinda Seberang which is claimed to be the basis for Samarinda City's establishment. Conducted with historical research methods, the result of this study found that the story of La Mohang Daeng Mangkona as the leader of the Bugis Wajo migrants to Samarinda is not based on valid historical sources. Following the result of this research, the researcher recommends to the Government of Samarinda City to revise and reconstruct the history of Samarinda City’s establishment based on the historiography method.